Strategies and Mechanisms to Create a Zero Sexual Violence Campus: Studies at UIN Mataram and IAIN Ponorogo - Muflikhatul khoiroh; Abd Syakur; Lilik Huriyah (MUWAZAH : jurnal kajian gender, 2023)
This study examines strategies and mechanisms for preventing and handling sexual violence at UIN Mataram and IAIN Ponorogo. This research belongs to the field research category with qualitative models. Data collection using interview and documentation methods. The data sources are the Rector or Vice-Rector, the Chairman of PSGA, and vocal points at the two universities. SWOT analysis is used to determine the strengths and weaknesses in realizing zero campus sexual violence. The results show, first, UIN Mataram is realizing a Zero campus of sexual violence through policy regulations and the fulfilment of gender-responsive infrastructure. Eight strategies and eight mechanisms were carried out. IAIN Ponorogo has seven strategies and four mechanisms. Second, based on the results of the SWOT analysis, it was found that UIN Mataram has twelve strengths, including the Rector of gender-responsive, the Head of LP2M being female who is sensitive and gender-responsive, a gender-responsive campus integrity pact, and six weaknesses, including officials dominated by men and do not yet have gender sensitivity and responsiveness, no budget for UIN care, lack of understanding of campus residents about sexual violence. IAIN Ponorogo has six strengths, including a female Rector whose gender perspective is qualified, the Rector's Decree on the prevention and handling of Sexual Violence, IAIN Ponorogo Care, and weaknesses, including the budget not being gender-responsive, human resources still lack capacity in handling Sexual Violence. Learning to realize zero campus sexual violence is a serious commitment of policymakers in implementing gender-responsive policies.